2014
DOI: 10.1158/1535-7163.mct-14-0171
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine Chemosensitizes Tumor Cells through Interaction with Cysteine 179 of IκBα Kinase, Leading to Suppression of NF-κB–Regulated Gene Products

Abstract: Recently, two different reports appeared in prominent journals suggesting a mechanism by which piperlongumine, a pyridine alkaloid, mediates anticancer effects. In the current report, we describe another novel mechanism by which this alkaloid mediates its anticancer effects. We found that piperlongumine blocked NF-kB activated by TNFa and various other cancer promoters. This downregulation was accompanied by inhibition of phosphorylation and degradation of IkBa. Further investigation revealed that this pyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…We also found that piperlongumine downregulated the constitutive activation of NF-kB in pancreatic cancer cell lines. These results on downregulation of NF-kB activation by piperlongumine are consistent with previous reports that piperlongumine inhibited activation of NF-kB in other cancer cell lines (30,39) and with reports that resveratrol (45), genistein (46), dihydroartemisinin (44), zyflamend (47), g-tocotrienol (48), curcumin (49), shikonin (9), and 3,3 0 -Diindolylmethane (50), all present within piperlongumine, are associated with NF-kB inactivation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that piperlongumine downregulated the constitutive activation of NF-kB in pancreatic cancer cell lines. These results on downregulation of NF-kB activation by piperlongumine are consistent with previous reports that piperlongumine inhibited activation of NF-kB in other cancer cell lines (30,39) and with reports that resveratrol (45), genistein (46), dihydroartemisinin (44), zyflamend (47), g-tocotrienol (48), curcumin (49), shikonin (9), and 3,3 0 -Diindolylmethane (50), all present within piperlongumine, are associated with NF-kB inactivation.…”
Section: Discussionsupporting
confidence: 92%
“…28), inhibit ubiquitin-proteasome system (37), arrest the cell cycle (38), inhibit the PI3K-Akt-mTOR signaling axis (38), and downregulate NF-kB activation (39). All these reports suggest that piperlongumine may have a strong potential for future use in cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4). PL exhibits a synergistic effect with various chemotherapeutic drugs, including cisplatin and paclitaxel, in ovarian, head and neck cancer (24,26,52). PL suppressed the expression of P-glycoprotein, ATP binding cassette subfamily B member 1, ATP binding cassette subfamily C member 1, survivin, and phospho-Akt, as well as the transcriptional activities of NF-κB and TWIST, which reversed doxorubicin resistance in a breast cancer cell line (53).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that PL was chemically inactivated by NAC in culture media through a conjugated addition reaction between the sulfhydryl group of NAC and the C2-C3 α,β-unsaturated imide group of PL; the resulting adduct, NAC-PL, was not senolytic. Based on these findings, caution is warranted when using NAC or similar compounds that contain a nucleophilic sulfhydryl group, such as dithiothreitol [54], as an ROS scavenger to study ROS inducers such as PL. In contrast, GT3, a potent ROS scavenger that does not react with PL, effectively blocked PL-induced ROS elevation but had no inhibitory effect on PL-induced SC death.…”
Section: Discussionmentioning
confidence: 99%